2014
DOI: 10.1111/1556-4029.12585
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Molecular Expression with Diel Rhythm of Oviposition in Calliphora vicina (Robineau‐Desvoidy) (Diptera: Calliphoridae) and Implications for Forensic Entomology

Abstract: This study explored the molecular mechanisms potentially underlying blow fly nocturnal oviposition. A behavioral study revealed that Calliphora vicina (Robineau-Desvoidy) (Diptera: Calliphoridae) possesses a diel rhythm of oviposition in light under 12:12 light/dark conditions. Reversal to 12:12 dark/light resulted in oviposition behavior changing to align with the adjusted regime in most females, but four of 59 experimental females lacked a diel rhythm of oviposition (were arrhythmic). Real-time PCR was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Moreover, despite the fact that L. cuprina is indeed found on carrion in countries such as Australia, South Africa, Thailand, and the USA, its forensic relevance also in these countries is proved just anecdotic in literature (Louw & van der Linde, 1993). Hence, we chose Calliphora vicina Robineau-Desvoidy (Diptera: Calliphoridae) as a target species for our study, as it is well known as a blow fly of forensic relevance on an almost global scale (Reiter, 1984;Smith, 1986;Anderson, 2000;Marchenko, 2001;Donovan et al, 2006;Amendt et al, 2007;Battan Horenstein et al, 2007;Park et al, 2009;George et al, 2014;Mohr & Tomberlin, 2014). Hence, we chose Calliphora vicina Robineau-Desvoidy (Diptera: Calliphoridae) as a target species for our study, as it is well known as a blow fly of forensic relevance on an almost global scale (Reiter, 1984;Smith, 1986;Anderson, 2000;Marchenko, 2001;Donovan et al, 2006;Amendt et al, 2007;Battan Horenstein et al, 2007;Park et al, 2009;George et al, 2014;Mohr & Tomberlin, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, despite the fact that L. cuprina is indeed found on carrion in countries such as Australia, South Africa, Thailand, and the USA, its forensic relevance also in these countries is proved just anecdotic in literature (Louw & van der Linde, 1993). Hence, we chose Calliphora vicina Robineau-Desvoidy (Diptera: Calliphoridae) as a target species for our study, as it is well known as a blow fly of forensic relevance on an almost global scale (Reiter, 1984;Smith, 1986;Anderson, 2000;Marchenko, 2001;Donovan et al, 2006;Amendt et al, 2007;Battan Horenstein et al, 2007;Park et al, 2009;George et al, 2014;Mohr & Tomberlin, 2014). Hence, we chose Calliphora vicina Robineau-Desvoidy (Diptera: Calliphoridae) as a target species for our study, as it is well known as a blow fly of forensic relevance on an almost global scale (Reiter, 1984;Smith, 1986;Anderson, 2000;Marchenko, 2001;Donovan et al, 2006;Amendt et al, 2007;Battan Horenstein et al, 2007;Park et al, 2009;George et al, 2014;Mohr & Tomberlin, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is much more common in sheep strike, where the larvae of this species infest living, injured tissue (Williams & Villet, 2014). Hence, we chose Calliphora vicina Robineau-Desvoidy (Diptera: Calliphoridae) as a target species for our study, as it is well known as a blow fly of forensic relevance on an almost global scale (Reiter, 1984;Smith, 1986;Anderson, 2000;Marchenko, 2001;Donovan et al, 2006;Amendt et al, 2007;Battan Horenstein et al, 2007;Park et al, 2009;George et al, 2014;Mohr & Tomberlin, 2014). Instead of saliva and sperm we used blood and putrefaction fluid as food sources for the flies because these traces are much more common at crime scenes and are regularly incorporated by blow flies.…”
Section: Introductionmentioning
confidence: 99%
“…The results declared the adjustment in gene expression and behaviour to adapt with the shifted regime of light. This is reverse the traditional assumption that oviposition by this species (C. vicina) always occurs during daylight [126].…”
Section: Gene Quantitationmentioning
confidence: 60%
“…Badania wykazały regulację ekspresji genów i zachowania w celu adaptacji do zmienionego oświetlenia. Wyniki te przeczą ogólnie przyjętemu założeniu, że u C. vicina owipozycja zawsze następuje za dnia [126].…”
Section: Gene Quantitationunclassified
“…Another factor to consider is whether or not the circadian rhythm is linked to oviposition behavior. Previous work in another blow fly, Calliphora vicina (Diptera: Calliphoridae), showed that eggs are more likely to be laid during light than in darkness [26]. Future work should not only investigate whether a pattern exists for C. megacephala, but also focus on determining a finer range of times.…”
Section: Discussionmentioning
confidence: 97%